The relationship between narrative microstructure and macrostructure: Differences between six- and eight-year-olds - Košutar Sara; Kramarić Matea; Hržica Gordana (Psychology of Language and Communication, 2022)
The current study aimed to investigate age-related differences in narrative abilities at the macrostructural and microstructural levels and to examine which microstructural aspects explain narrative macrostructure at ages six and eight. Oral narratives were elicited from 89 Croatian monolingual children using the Multilingual Assessment Instrument for Narratives (MAIN). At the microstructural level, the measure of lexical diversity D, clausal density, and mean length of clause were assessed. Macrostructure was assessed using the standardized MAIN scoring procedure. We found differences between the two age groups in lexical diversity, clausal density, and macrostructure, with eight-year-olds scoring higher on all measures. Variance in the macrostructure was explained to a significant extent by lexical diversity in the case of six-year-olds, and by both lexical diversity and clausal density in the case of eight-year-olds. Our results suggest that six-year-olds rely mostly on lexical abilities when telling a story, while eight-year-olds also draw on syntactic abilities.